The wife app [large type] - Mackler, Carolyn (Thorndike Press large print top shelf., 2023)
"Lauren wakes up one morning and stumbles on a dirty secret that explodes her marriage. Madeline has a penthouse apartment, a perfect daughter, and no-string-attached romps with handsome men. When she learns she might loose her child to her ex in England, it stirs up a decade-old personal tragedy. Sophie obsessed over her ex-husband's Family 2.0. It starts as a joke as Lauren, Madeline, and Sophie rail against everything wives do for free. Let's build an app that monetizes the mental load. And maybe get revenge on our exes in the process? Soon, the Wife App is born, but the consequences are bigger than anything Lauren, Madeline, or Sophie could have expected."--Back cover.